2013
DOI: 10.1016/j.bbi.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated relationship of inflammation and oxidative stress in major depression

Abstract: Chronic inflammation and oxidative stress have been implicated in the pathophysiology of Major Depressive Disorder (MDD), as well as in a number of chronic medical conditions. The aim of this study was to examine the relationship between peripheral inflammatory and oxidative stress markers in un-medicated subjects with MDD compared to non-depressed healthy controls and compared to subjects with MDD after antidepressant treatment. We examined the relationships between IL-6, IL-10, and the IL-6/IL-10 inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(127 citation statements)
references
References 115 publications
(146 reference statements)
3
118
0
1
Order By: Relevance
“…In certain chronic disease states, both of these systems remain activated and may, indeed, form a positive self-sustaining feedback loop or a Bco-activation^state [44]. Over time, such co-activation may lead to a higher risk of depression [5]. Third, Hs-CRP may contribute to the development of depression via an increased white matter hyperintensity burden.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In certain chronic disease states, both of these systems remain activated and may, indeed, form a positive self-sustaining feedback loop or a Bco-activation^state [44]. Over time, such co-activation may lead to a higher risk of depression [5]. Third, Hs-CRP may contribute to the development of depression via an increased white matter hyperintensity burden.…”
Section: Discussionmentioning
confidence: 98%
“…A large body of evidence suggests that depression is accompanied by activation of inflammatory pathways, reflected by an increased level of inflammatory cytokines [5]. Baune et al [6] found that IL-8 was associated with the first onset of depressive symptoms, whereas plasminogen activator inhibitor-1 (PAI-1) could be regarded as a marker of remitted depression, and Becking et al [7] found that depressed men who developed manic symptoms during Chao-Zhi Tang and Yu-Ling Zhang contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have described the balance between pro-and antiinflammatory factors to be a more accurate reflection of the inflammatory environment [58,59]. Due to significant interindividual differences in the concentrations of pro-or antiinflammatory factors, here, we evaluated the ratio of pro-to anti-inflammatory factors, which provided a useful measure of the net immunological effect of the circulating cytokines and/ or other factors associated with damage.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione in particular plays a major role in the redox process (Schafer and Buettner, 2001) and affects the brain by directly detoxifying drugs, ROS, and electrophilic xenobiotics, being a source of cysteine, promoting neurodevelopment and enhancing excitatory glutamatergic neurotransmission (Kohr et al, 1994;Meister, 1988;Shi et al, 2000). Oxidative stress and inflammation contribute notably to major depression (de Morais et al, 2014;Rawdin et al, 2013). In a meta-analysis based on 4908 subjects, depression was associated with high oxidative stress status and with an imbalance towards oxidative markers rather than anti-oxidants (Palta et al, 2014).…”
Section: Neuroinflammation and Oxidative Stressmentioning
confidence: 99%